Advertising as a Linguistic and Cultural Phenomenon (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article is devoted to the study of advertising language as a cultural phenomenon and analyzes advertising texts in Uzbek and French. Advertising is important not only as a means of presenting products or services, but also as a means of reflecting social and cultural values. The article studies the linguistic features, styles and cultural contexts of advertising texts in Uzbek and French. It also analyzes the specificity of advertising language, its role in communicating with the audience, and how culture affects the content of advertising. It examines how the specific aspects and traditions of Uzbek and French cultures are expressed in advertising language, as well as the importance of language and its communicative functions in this process. The results of this study contribute to a deeper understanding of the relationship between advertising language and culture and provide an opportunity to look at advertising practices from a new perspective.